Neonatal Neuroblastoma with Pepper Syndrome: A Case Report - Shishir Kumar Jha; Reena Tomar; Yogesh Kumar Sarin (EL-Med-Pub, 2019)
Pepper syndrome can be associated with significant hepatomegaly causing an increase in abdominal volume to the extent of causing respiratory distress. Here, we present a neonate who succumbed to classical Pepper syndrome.